Biological units of antimicrobial resistance and strategies for their containment in animal production. Issue 7 (19th May 2022) - Muurinen, Johanna; Cairns, Johannes; Ekakoro, John Eddie; Wickware, Carmen L; Ruple, Audrey; Johnson, Timothy A
Abstract: The increasing prevalence of antimicrobial-resistant bacterial infections has ushered in a major global public health crisis. Judicious or restricted antimicrobial use in animal agriculture, aiming to confine the use for the treatment of infections, is the most commonly proposed solution to reduce selection pressure for resistant bacterial strains and resistance genes. However, a multifaceted solution will likely be required to make acceptable progress in reducing antimicrobial resistance, due to other common environmental conditions maintaining antimicrobial resistance and limited executionary potential as human healthcare and agriculture will continue to rely heavily on antimicrobials in the foreseeable future. Drawing parallels from systematic approaches to the management of infectious disease agents and biodiversity loss, we provide examples that a more comprehensive approach is required, targeting antimicrobial resistance in agroecosystems on multiple fronts simultaneously. We present one such framework, based on nested biological units of antimicrobial resistance, and describe established or innovative strategies targeting units. Some of the proposed strategies are already in use or ready to be implemented, while some require further research and discussion among scientists and policymakers. We envision that antimicrobial resistance mitigation strategies for animal agriculture combining multiple tools would constitute powerful ecosystem-level interventions necessary to mitigate antimicrobial resistance. Abstract : Review of nested biological units of antimicrobial resistance and established or novel interventions that could be used to target each of these units: novel antimicrobial resistance mitigation strategies in addition to reduced antimicrobial use.